Estimation of Myopia among School Children of Bangalore, India - Ashwini, D. L.; Khan , Asif Ali; Karuna , S. M. (Current Overview on Disease and Health Research Vol. 11, 2023)
This chapter aims to estimate the myopia among school children of Bangalore region, Karnataka, India. Myopia is one of the most common visual problems that affects both children and adults. High myopia increases the risk of developing irreversible vision loss due to pathologic changes in the retina, as well as the risk of glaucoma, cataract, and amblyopia. The current study included students aged 5 to 15 years from urban and rural schools in the Bangalore region. A total of 3038 students were screened from six different schools, with 1510 girls and 1528 boys. The students were subjected to basic eye examinations such as visual acuity and dry retinoscopy. In addition, the power of the glasses the children were already wearing for the past correction was recorded. According to the findings of this study, 4% (241) of the 6076 eyes screened had myopia. Myopia affected 3.18% (94) of 2954 rural children and 4.71% of 3122 urban children. It was concluded that urban school children in Bangalore, Karnataka, had a higher frequency of myopia than rural school children.